A new species of Pacifigorgia (Coelenterata: Octocorallia: Gorgoniidae) from Panamá - Breedy, Odalisca; Guzmán, Héctor M. (Zootaxa, 2003)
Pacifigorgia rubinoffi, a new shallow water species of the family Gorgoniidae from the Pacific Panamá, is described and illustrated. Known from several localities around the Gulf of Chiriquí, it is patchy in distribution, ranging from 1-5 m in depth. The colony is characterized by multiple fans, closed meshwork, lack of distinct midribs, a deep orange color of both colony and sclerites, low occurrence of spindles with acute and bent ends, large asymmetric rods, and the occurrence of barrels. The new species is illustrated in detail with scanning electron micrographs, photomicrographs and color photographs.